Limits on absorption from a 332-MHz survey for fast radio bursts. Issue 3 (4th March 2020) - Rajwade, K M; Mickaliger, M B; Stappers, B W; Bassa, C G; Breton, R P; Karastergiou, A; Keane, E F
ABSTRACT: Fast radio bursts (FRBs) are bright, extragalactic radio pulses whose origins are still unknown. Until recently, most FRBs have been detected at frequencies greater than 1 GHz with a few exceptions at 800 MHz. The recent discoveries of FRBs at 400 MHz from the Canadian Hydrogen Intensity Mapping Experiment (CHIME) telescope have opened up possibilities for new insights about the progenitors while many other low-frequency surveys in the past have failed to find any FRBs. Here, we present results from an FRB survey recently conducted at the Jodrell Bank Observatory at 332 MHz with the 76-m Lovell telescope for a total of 58 d. We did not detect any FRBs in the survey and report a 90${{\ \rm per\ cent}}$ upper limit of 5500 FRBs per day per sky for a Euclidean Universe above a fluence threshold of 46 Jy ms. We discuss the possibility of absorption as the main cause of non-detections in low-frequency (<800 MHz) searches and invoke different absorption models to explain the same. We find that Induced Compton Scattering alone cannot account for absorption of radio emission and that our simulations favour a combination of Induced Compton Scattering and Free-Free Absorption to explain the non-detections. For a free–free absorption scenario, our constraints on the electron density are consistent with those expected in the post-shock region of the ionized ejecta in superluminous supernovae.